2020
DOI: 10.1007/s11356-020-07672-0
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter on foliage of Betula pendula, Quercus robur, and Tilia cordata: deposition and ecophysiology

Abstract: Trees in urban and industrial areas significantly help to limit the amount of particulate matter (PM) suspended in the air, but PM has a negative impact on their life. The amount of PM gathered on leaves depends on quantity, size, and morphology of leaves and can also be increased by the presence of epicuticular waxes, in which PM can become stuck or immersed. In this study, we determined the ability of PM to accumulate on leaves in relation to the species of tree and PM source. We tested saplings of three com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…Plant material was taken from 2-5 adult apple trees at each site. Leaves and fruits ((about 50 mg)) were taken from different quarters of canopy as recommended in (Wang et al 2015;Tošić et al 2016, Krupnova et al 2020aŁukowski et al 2020). All leaf and fruit samples were washed in freshwater to eliminate dust, dirt and insects.…”
Section: Methodsmentioning
confidence: 99%
“…Plant material was taken from 2-5 adult apple trees at each site. Leaves and fruits ((about 50 mg)) were taken from different quarters of canopy as recommended in (Wang et al 2015;Tošić et al 2016, Krupnova et al 2020aŁukowski et al 2020). All leaf and fruit samples were washed in freshwater to eliminate dust, dirt and insects.…”
Section: Methodsmentioning
confidence: 99%
“…Sehmel et al found that when the dust-containing air flow passed through the tree crown, some dust with larger particles was blocked by the branches/leaves and fell, and could be returned to the air due to the action of wind and other external forces, while the other part remained on the surface of the branches and leaves [47]. The amount of PM gathered on leaves depends on the quantity, size, and morphology of the leaves, and can also be increased by the presence of epicuticular waxes, in which PM can become stuck or immersed [48]. In the closed multi-layered structural forest, the vertical structure of the vegetation was complex and there were many plant species, which to some extent hinders the airborne particulate matter from settling to the ground [49].…”
Section: The Influence Of Vegetation Structure On the Concentration Of Airborne Particulate Matter At Different Heightsmentioning
confidence: 99%
“…The accumulation of air pollutants and airborne PMs on leaf surfaces is dependent on the plant species, leaf size and structure, but is also affected by the types of waxes which make up the cuticle, the hairs covering the leaf and leaf smoothness [46,47,182,183]. Both PMs and hydrocarbon contaminants accumulating on the leaf surface affect bacterial communities.…”
Section: Phylloremediationmentioning
confidence: 99%